Respuesta :

Answer:

x = -0.04166666667

Step-by-step explanation:

2x + 8 * 96 = 0

2x * 96 = -8

x/2 * 96 = -8/2

x * 96 = -4

x = -4/96

x = -0.04166666667

Answer:

198

Explanation:

The way to solve this equation is by using the "X=96" from moving it to the x in the equation witch makes it "2(96) + 6" When the variable is after the letter like 2x it always means multiplying. So when you multiply 2(96) together you get 192, then you would add 6+192 which would equal 198. I hope I helped! :D